Study of radiation dose induced by cosmic-ray origin low-energy gamma rays and electrons near sea level. (February 2015) - Mrdja, D.; Bikit, I.; Bikit, K.; Slivka, J.; Anicin, I.
Abstract: For a long time, it has been known that low-energy continuous gamma radiation is present in open air at the Earth's surface. In previous investigations it was assumed that this radiation is produced almost exclusively by gamma photons emitted due to the natural radioactivity, which are backscattered by air above ground. We show that significant amount of this radiation (related to energy region 30–300 keV) that peaks at about 90 keV, is produced by cosmic-rays, with the photon flux of about 3000 m −2  s −1 . We find that the contribution of this omnipresent low-energy gamma radiation of cosmic-ray origin, including the corresponding low-energy electron flux, to the doses of general population are non-negligible components of overall doses induced by cosmic rays near sea level. Highlights: Low-energy continuous cosmic origin radiation near sea-level was investigated. The fluxes of low-energy photons and electrons were estimated. The annual doses for humans from low-energy cosmic-origin radiations were found.